Post-operative health related quality of life assessment in scoliosis patients - Chan, C.Y.; Kwan, M.K.; Saw, L.B.; Deepak, A.S.; Chong, C.S.; Liew, T.M.; Lee, C.S. (Malaysian Medical Association, 2008)
Adolescent Idiopathic Scoliosis is a spinal deformity which affects patients self image and confidence. Surgery is offered when the curve is more than 50 degrees based on its likelihood of progression. Studies on the radiological outcome of scoliosis correction are abundant. Therefore, it is the objective of this study to evaluate the health related quality of life in scoliosis patients who had undergone surgical correction in University Malaya Medical Center, Kuala Lumpur, Malaysia using Scoliosis Research Society-22 (SRS-22) patient questionnaire. This is a prospective evaluation of SRS-22 scores of thirty eight patients operated in our center over the past five years with a minimum follow up of one year. There were thirty two females and six males. Twenty six (68.4) were Chinese, eight (21.1) Malay and four (10.5) Indian patients. The age of the patients ranged from twelve to twenty eight years, with a mean age of 18.4 Â± 3.5. Based on the King and Moeâs classification, sixteen patients had Kingâs 3 curve. The mean pre-operative Cobb angle was 68.6o and post-operative Cobb angle was 35.8o. The average curve correction was 48.5. The overall score for SRS-22 was 4.2. The SRS-22 scores were highest for the pain domains and lowest for the functional domains. Satisfaction domain scored 4.3. The function domain scored significantly higher in those who have twenty four months or less follow up duration. Curve magnitude and the amount of correction did not significantly alter the SRS scores. In conclusion, patients were satisfied with the outcome of their operation. Although pain was common, the intensity of the pain was minimal. The amount of curve correction did not correlate with the quality of life after operation.